2020
DOI: 10.1007/978-981-15-6964-7_6
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study of the Tokyo Emissions Trading Scheme: An Ex Post Analysis of Emissions from University Buildings

Abstract: The Tokyo Emissions Trading Scheme (ETS) is the first cap -and-trade program of CO2 emissions in Asia, and it is unique in regulating commercial and service sectors. We examine the impacts of the Tokyo ETS on CO2 emissions and energy consumption by universities in the first phase. Focusing on universities allows us to estimate the effects of the Tokyo ETS separately from the economic stagnation Japan experienced after the Great East Japan Earthquake in 2011 because universities are less likely to be affected b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Data on impacts are scarcer than ex-ante information, and the Tokyo case is an example. Electricity prices, regulatory decisions, and extreme events are possible external causes to consider for emission reduction [42].…”
Section: Carbon Pricing Initiatives At the Local Levelmentioning
confidence: 99%
“…Data on impacts are scarcer than ex-ante information, and the Tokyo case is an example. Electricity prices, regulatory decisions, and extreme events are possible external causes to consider for emission reduction [42].…”
Section: Carbon Pricing Initiatives At the Local Levelmentioning
confidence: 99%
“…The emissions trading scheme at the Japanese national level has not yet been introduced (for more details, see Abe & Arimura, 2021Arimura & Matsumoto, 2021;Hamamoto, 2021;Kurachi, Morishima, Kawata, Shibata, Bunya, & Moteki, 2022;Sadayuki & Arimura, 2021;International Carbon Action Partnership, 2022a;Asian development Bank, 2016;Poupard, Fetet, & Postic, 2022, etc.). The Tokyo-ETS is also the first emissions scheme worldwide to cover the commercial sector.…”
Section: Some Aspects Of the Tokyo-etsmentioning
confidence: 99%
“…Since its launch in 2010, universities located in Tokyo prefecture have been regulated by this regional instrument. Despite that its market price has been one of the lowest in the world at around $2.60 per ton of carbon, Abe and Arimura (2021) revealed that the amount of CO 2 emission had been actually reduced by 3%–5% in the participating universities compared to the universities in other prefectures during its first phase (2009–2013). Entering its third phase, carbon pricing as a CO 2 reduction instrument is contributing to giving price advantage in renewable energy and increasing investment in renewable energy technology in the participating universities (Kojima and Asakawa, 2021).…”
Section: Opportunities In Higher Education Institutionsmentioning
confidence: 99%